PENGARUH KEMAMPUAN TEKNOLOGI INFORMASI, KEMUDAHAN, RISIKO DAN FITUR LAYANAN TERHADAP MINAT NASABAH DALAM MENGGUNAKAN INTERNET BANKING (Studi Empiris Pada Nasabah Bank Rakyat Indonesia Di Kota Banjarmasin) - Ida Mentayani; Rusmanto Rusmanto; Rahmiati - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aims to provide empirical evidence about the influence on the effect of technological capabilities, ease, risks, and service features to customers' interest in using internet banking at Bank BRI in Banjarmasin. The population in this research are all customers who use internet banking BRI BRI in the unit In Banjarmasin, Teluk Dalam unit, Pasar Lama unit and unit Belitung. Sampling technique used was quota sampling, in which the sample is chosen technique considering a relatively short research time and research objects consist of three units of BRI office. Additionally customers who use internet banking are visiting the office unit is also relatively small, so in this study the researchers gave the quota of each office unit of 20 people. The sample taken is 60 customers who use internet banking at BRI unit Teluk Dalam, in the pasar lama and the BRI BRI unit Belitung. Types and data sources of primary data obtained through a questionnaire distributed at bank customers as respondents, supplemented with secondary data obtained from various references. Multiple Linear Regression method used to test the hypothesis that has been proposed. The results of the research provide empirical evidence that the ability of information technology partially affect the interest of customers using internet banking, convenience partially affect the interest of customers using internet banking, risk is partially affect the interest of customers using internet banking, service features partially affect the interest of customers using internet banking. While simultaneously the ability of information technology affect the interest of customers using internet banking. The coefficient of determination adjusted R Square showed a value of 0.553 or 55.3%. Shows that the value of bank customers' interest in using internet banking can be explained by the ability of information technology, convenience, risk and service features of 55.3%. If adjusted R Square has a value> 0.5 s / d 1, is to have a strong influence.